Supervolcano the truth about yellowstone - Simpson, Alisdar; Sutton, Lee; Guetin, Roger; Scott, Fiona
Uncovers the science of the giant volcano simmering beneath Yellowstone National Park in the USA. Leading geologists and volcanologists from around the world contribute. Directly following Supervolcano, a two-episode documentary reveals the cutting-edge research that informed the drama. Meet the experts who monitor the behaviour of the Yellowstone supervolcano, who face the awesome responsibility of predicting when the next super-eruption might next take place - and advising on what will happen when it does. The programme goes behind the scenes to reveal the work being done to try to understand the sequence of events that could one day culminate in this apocalypse, and to calculate the global fallout that would follow it. Written by BBC